2016
DOI: 10.1111/fog.12158
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in otolith increment width trajectories and the effect of temperature on the daily growth rate of young sardines

Abstract: We studied the otolith microstructure and growth of sardine, Sardina pilchardus, in the North Aegean Sea (eastern Mediterranean Sea), using samples of larvae and juveniles that had hatched in winter (NovemberJanuary) and winter-spring (February-May), respectively. The juveniles had developed during an extended period coinciding with marked pelagic ecosystem changes (from winter, mixed conditions to summer, stratified waters). To examine the relationship between environmental changes and the observed variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
2
16
0
1
Order By: Relevance
“…the length at metamorphosis, decreases with temperature (Fuiman et al 1998), and morphological transitions are more abrupt and synchronized among traits at higher temperatures (Nikolioudakis et al 2014b). This is, for example, evident in the otolith growth pattern, which changes from increasing to decreasing increment widths during metamorphosis: increment width trajectories are more 'leptokurtic' at high temperatures and 'platykurtic' at low temperatures (Schismenou et al 2016).…”
Section: Temperature Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…the length at metamorphosis, decreases with temperature (Fuiman et al 1998), and morphological transitions are more abrupt and synchronized among traits at higher temperatures (Nikolioudakis et al 2014b). This is, for example, evident in the otolith growth pattern, which changes from increasing to decreasing increment widths during metamorphosis: increment width trajectories are more 'leptokurtic' at high temperatures and 'platykurtic' at low temperatures (Schismenou et al 2016).…”
Section: Temperature Effectsmentioning
confidence: 99%
“…In the eastern Mediterranean, Schismenou et al (2014Schismenou et al ( , 2016 studied the effect of temperature and other ecosystem parameters on the daily growth rate of European anchovy and European sardine in the field using otolith microstructure analysis and simulations of a hydrodynamic-biogeochemical model. Using a statistical modelling approach that accounted for the uncoupling of otolith and somatic growth (the 'inherent otolith growth'), they found that the co-occurring species had the same temperature optima for early growth, at about 24.5°C.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…The number of daily increments is largely determined by the length of the growing season, while the width of daily increments is highly associated with the environmental temperature (Ding, 2012). In natural systems, particularly those very sensitive to global warming (e.g., Siling Co), temperature could be the main factor affecting daily increment width of fish otolith, and potentially incorporated with other factors such as food resources (Campana & Neilson, 1985;Schismenou et al, 2016;Wenger, Whinney, Taylor, & Kroon, 2016). However, it is almost impossible to retrieve data of historical food availability of G. selincuoensis each year, which relies on long-term and continuous monitoring on food resources.…”
Section: Access Constraints and Safety Considerations Meant That Sampmentioning
confidence: 99%
“…Thermal tolerance is expected to increase as fish grow up to the juvenile and adult stages. A recent work conducted in the Mediterranean Sea (Schismenou et al 2016) has found that larvae occurred in areas of SST ranging from 13 to 17°C, and a linear and positive relationship of sardine larvae growth rate was found with temperature. In contrast, sardine juveniles developed in a wider range of temperatures (12−27°C) and had a dome-shaped growth response, with an optimum at around 24°C.…”
Section: Discussionmentioning
confidence: 94%